Study the Prevalence of Helicobacter Pylori among Children in Wasit Province - Al-Mkhadhree, Enass Abdul Kadhum Abed (American Journal of Biology and Natural Sciences, 2024)
The bacterium H. pylori is commonly found in the stomachs of humans and other primates. It is a gram-negative, spiral-shaped bacterium that thrives in low-oxygen conditions that causes systemic infections in stomach. Given this fact, One hundred thirty four samples were collected from children (6-12 years old) suffering from weakness, emaciation, digestive disorders, stomach and colon problems, frequent vomiting, abdominal pain. The sample were collected by the specialists of the Department of Internal Medicine, the Section of Gastrointestinal from Disease and the outpatient center at Al-Karama Teaching Hospital, Al-zahraa Teaching Hospital during the period from 3rd March 2024 to 3rd November 2024. The current study showed, the Prevalence of H. pylori was 106 /134 (79.1 %) their age 6 to 12 years. Regarding of Diagnosis H. pylori the study indicated that 76.1% (102 out of 134 ) of the specimens tested positive for the Assure H. pylori Ab Rapid Test , The result of the stool antigen test (SAT) yielded positive results in 98 out of 134 specimens, indicating a positivity rate of (83.1%),while, The result of Urea Breath Test revealed that from 102 tested specimens (86.4%) were positive . and The results of PCR technique indicated that 88% (118 out of 134) of the specimens were positive to this test. Regarding the hematological parameters of the H. pylori test among participants who had positive test compared to participants who had negative test compared. The mean levels of hemoglobin (10.4±3.8vs. 13.1±2.5 g/dL), red blood cell count (RBC 3.9*109±0.9 vs.4.4*109±0.9/μL), white blood cell count (WBC 11.2*109±1.9/L vs.6.7*109±1.8/L) and hematocrit (Hct 34.1±6.2 vs. 39.4±6.0 %) were significantly lower among participant has positive test compared to participant has negative. The result this study showed many factors that increase the risk of H. pylori infection in children such as place of residence, source of drinking water, consumption of fast food and chips, regular hand washing before meals, tooth decay. the study Concluded there are high Prevalence of Helicobacter Pylori among children in in Wasit province.